Are left atrial diverticula and left-sided septal pouches relevant additional findings in cardiac CT? Correlation between left atrial outpouching structures and ischemic brain alterations. (15th October 2020) - Celik, Erkan; Pennig, Lenhard; Laukamp, Kai Roman; Hammes, Jochen; Maintz, David; Kabbasch, Christoph; Abdullayev, Nuran; Bunck, Alexander Christian; Achenbach, Tobias; Caldeira, Liliana; Hickethier, Tilman
Abstract: Purpose: To evaluate the correlation between left atrial diverticula (LAD) and left-sided septal pouches (LSSP) with ischemic brain alterations in MRI. Methods: A retrospective analysis of 174 patients who received both, a dedicated cardiac CT angiography (CCTA) and a brain MRI examination was performed. Two radiologists independently reviewed all examinations for the presence of LAD and LSSP as well as ischemic alterations of the brain. Subsequently, the correlation between these cardiac and cerebral findings as well as to other potentially related risk factors was assessed. Results: 71 LAD (total prevalence 41%) and 65 LSSP (total prevalence 37%) were identified in 174 patients. Combined prevalence was 10%. Ischemic brain alterations were found in patients with a LAD in 42.3% (30/71) and with a LSSP in 64.6% (42/65). Patients without any anatomical variant in the left atrium showed ischemic brain alterations in 39.4% (26/66). The presence of a LSSP was associated with an increased risk for ischemic brain alterations in multivariate logistic regression analysis after adjusting for other risk factors (OR = 3.57, 95% CI = 0.51–2.09, p  <  .01). Conclusion: In our study cohort LAD and LSSP are highly prevalent anatomical structures within the left atrium. Patients with LSSP showed an approximated 3.5-fold higher probability for ischemic brain alterations. Therefore, LSSP should be considered as a potential risk factor for cardioembolic strokes and its presence should be stated in cardiac CT reports. Highlights: LAD and LSSP are highly prevalent structures within the left atrium. LSSPs are associated with an increased risk for ischemic brain alterations. LSSP should be considered as a potential risk factor for cardioembolic stroke.